FEEDER NETWORK ANALYSIS OF MASS RAPID (STUDY CASE : CITY OF SURABAYA) - Budi Prakoso, Wahyu
High intensity amount of Surabaya trip is not supported by the condition of accessibility of existing public transport infrastructure, where the existing public transport backbone accomodate with angkot and bus which are considered less optimal from integrated multimodal system. This caused dominance of private modes, especially motorbikes. Mass rapid transit system became the main solution from the Surabaya City Government to solve the problem. Mass rapid transit of Surabaya (AMC) linked from north-south corridor which have a characteristics length ± 23 km with 26 stop stations, using a dedicated Tram line (ROW Type B). The goals of this research are to analyze the effect of mass rapid north-south corridor development to private and public network in Surabaya based on their performance, and then analyzed to modify the feeder network (consist of angkot and bus) for increase passenger purposed. In this research, EMME 4 is utilized to analysis of transport network modelling. The development of mass rapid north-south corridor has an impact to increase mode share 1.37% in the city of Surabaya. Passengers in the north-south of Surabaya prefer using mass rapid of Surabaya (AMC) than using a bus. Bus line indicated 11.9% decrease in total passenger, because most of bus route are overlapping with AMC which makes the bus have no competitiveness. Furthermore, mass rapid of Surabaya (AMC) makes public tranportation more effective, average transit time shorther than before. But, AMC has a negative impact, it will makes auto vehicle must long distance travelled, because there is a reduction of road capacity along the AMC route. To optimize the existing transportation, it is necessary to modify the feeder route, in this research 5 feeder routes which has 30-70% overlapped and indicated decrease performance indicator are modified. So the role of feeder network becomes more optimal, based on additions amount of total passenger in Surabaya.